Examining Al-Wujuh Wa Al-Nazair and Its Role in Understanding the Qur’an - Munajib, Achmad (Proceeding International Conference on Religion, Science and Education, 2022)
The Qur’an always gives birth to new interpretations of the meaning contained in it from time to time because it is the main legal basis for Islamic law that is true for every era and place, because of the many meanings contained in the Qur’an, it appears the study of al-wujuh wa al-nazair, the purpose of this observation is to review al-wujuh wa al-nazair and know its role in understanding the verses of the Qur’an. This research is library research. The method used is content analysis which is used to explore understanding and information as well as the opinions of scholars and commentators of the Qur’an. The result of this discussion is that al-wujuh is a word that has similarities in letters and forms in various editorials of the verse but contains different meanings, while al-nazair is one meaning expressed by many words in the Qur’an. As for the rules of meaning mentioned by some scholars, namely "all these words in the Qur’an have such meaning." and "all these words in the Qur’an have such meaning, except this verse", the historical discussion of al-wujuh wa al-nazair has occurred in the early Islamic generation, but the discussion is complete in a new book. Appeared in the II century H. The urgency of al-wujuh wa al-nazair is very significant in interpreting and understanding the Qur’an, and it can be said that someone can be wrong in understanding the Qur’an if without a proper understanding. True about al-wujuh wa al-nazair.